Strategi peningkatan penjualan sparepart dengan mengintegritaskan analisis SWOT dan metode AHP pada CV. Jaya Maju Perkasa - Imanuddin, Rahmat; Hadidjija, Kusno; Utomo, Eko Budi; Putra, Muhammad Hengki Riawan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Human resources are one of the resources in the form of humans based on energy or thoughts that are used to develop a better company in the future. If the human resources used are less skilled or less good, it will greatly affect the products or work results provided. This is felt by a manufacturing company in the furniture sector, namely PT. Omega Mas. In order to understand the level of employee performance produced, PT. Omega Mas needs to conduct an employee performance assessment. In this employee performance assessment, the rating scale method with AHP is used. While in collecting data using questionnaires and brainstorming. The results obtained were that there were 5 employee performance assessment criteria with each criterion having 3 sub-criteria. These criteria are self-maturity, work attitude, cooperation, discipline, and Work Results. In the weight of employee performance assessment, the dominant one is Work Quantity with a weight value of 0.311. In the performance results, there were 6 employees who had very good scores, 47 employees had good scores, and 80 other employees had sufficient scores.